PENDEKATAN KUANTITATIF, KUALITATIF DAN KRITIS SEBAGAI ALAT BANTU DALAM KAJIAN LIVING HADIS - Mohamad Hudaeri (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2016)
Even though some certain religions are perceived to be originated from God, they can not be detached from human understanding and exegesis. It is for this reason that any kind of perceptions on any religion, realized or not, relies upon the paradigm used. Adherents of a religion commonly used some idealistic paradigms, which are meant to embed and maintain the faith. On the other hand, researchers of religion(s) used an objective paradigm, particularly social sciences. Under the later paradigm, there are three approaches: qualitative approache, quantitative approache, and critical approache. Various phenomena of a religion (in this case, Islam) can be comprehended with any of these approaches.